Sistema de apoyo terapéutico para la recuperación de la autonomía física en la cotidianidad ajena a los entornos médicos (2022)
S.A.FI.RE (Autonomous Physical Assistance and Recovery System) is a project focused on providing a tool that helps those who are in a process where their physical autonomy (capabilities and skills of their own and individual character) is gradually lost due to factors such as illnesses, accidents, injuries or simply as a consequence of the passing of the years.